ANALISIS PENGELOLAAN ANGGARAN PENDAPATAN DAN BELANJA DESA (APBDES) UNTUK MENILAI TRANSPARANSI DAN AKUNTABILITAS DI DESA TANJUNG LIMAU KECAMATAN MUARA BADAK TAHUN 2019 - Sawin Ester Jhoni; Erni Setiawati (OBOR: Oikonomia Borneo, 2021)
The purpose of this study is to find out how the management of the revenue and expenditure budget of Tanjung Limau village, Muara Badak district in 2020 has been carried out transparently and to find out whether the management of the income and expenditure budget of Tanjung Limau village, Muara Badak district in 2020 has been carried out in an accountable manner. Villages are the pioneers of an autonomous and fully sovereign democratic system and have their own social norms. Villages as autonomous regions are given special rights, such as managing village budgets. Village financial management is derived in the form of village policies in the form of the Village Revenue and Expenditure Budget (APBDesa). This study aims to determine the transparency and accountability of the management of the village budget and expenditure income (APBDesa) in Tanjung Limau village, Muara Badak sub-district. This type of research is to use a qualitative approach in the type of case study. The research method is, the data sources used in this research are primary data sources and secondary data sources. Primary data sources were obtained through interviews and secondary data sources were obtained from books, internet, and related documents. Informants in this study were the village head, village secretary, village treasurer, head of development, BPD, RW, RT, and representatives of community leaders in Tanjung Limau village, Muara Badak district. The result of this research is that the management of APBDesa in Tanjung Limau village, Muara Badak sub-district is already based on the principles of transparency and accountability, although it is not fully in accordance with existing regulations. Thus, it is necessary to carry out continuous improvements while still adjusting to the situation and conditions as well as the development of the prevailing laws and regulations